The first zoeal stage of two species of Grapsidae (Decapoda, Brachyura) and a key to such larvae from the Brazilian coast - Fransozo, A.; Cuesta, J. A.; NegreirosFransozo, M. L. (Brill Academic Publishers, 1998)
First zoeal stages of the grapsinid Goniopsis cruentata (Latreille, 1803) and the sesarminid Aratus pisonii (H. Milne Edwards, 1837), are described and illustrated. Grapsinae zoeae can be distinguished from the other grapsid larvae by the absence of lateral spines on the carapace and the reduction of the antennal exopod to a small seta. A key to the first zoeal stage of the Brazilian coast Grapsidae is provided.